Mini cold storage using the parabolic solar trough: An appropriate technology for perishable agricultural product - Janella Siddhartha Yadav; Korakana Shirisha; Chinthada Manikanteswar Rao (Mechanical Engineering for Society and Industry, 2022)
Limited storage of perishable agricultural products is a common problem for small-scale farmers. Therefore, our approach for this problem is to develop a low operating cost mini cold storage using solar energy. The integration of solar thermal energy with vapor absorption refrigeration systems was studied. In vapor absorption systems, heat energy is taken as the source of input energy and the performance characteristics depend on heat energy supplied and pump work used. The novelty of our project is that it uses a parabolic solar heat collector to run a vapor absorption refrigeration system using heat energy extracted from solar energy. In this cyclic process, the refrigerating effect is produced. By utilizing this mini cold storage system, tomatoes can be stored for four weeks whereas, with room temperature storage, it only lasts one week. This appropriate technology promises small-scale farmers to keep their perishable agricultural products for several weeks without additional storage costs.